MCPIP1 regulates RORα expression to protect against liver injury induced by lipopolysaccharide via modulation of miR‐155. Issue 9 (27th February 2019) - Li, Zhenzhen; Han, Shichao; Jia, Yanhui; Yang, Yunshu; Han, Fu; Wu, Gaofeng; Li, Xiaoqiang; Zhang, Wei; Jia, Wenbin; He, Xiang; Han, Juntao; Hu, Dahai
Abstract: Liver injury plays vital roles in the development of inflammation and organ dysfunction during sepsis. MCP‐1‐induced protein 1 (MCPIP1), as an endoribonuclease, is a critical regulator for the maintenance of immune homeostasis. However, whether MCPIP1 participates in the septic liver injury remains unknown. The aim of this study was to investigate the role of MCPIP1 in lipopolysaccharides‐induced liver injury and the underlying modulatory mechanisms. Quantitative real‐time polymerase chain reaction and immunoblotting were used to determine proinflammatory cytokines, MCPIP1, retinoid‐related orphan receptor α (RORα), miR‐155, and related protein from nuclear factor‐κB (NF‐κB) pathway expression. Dual luciferase reporter assay was used to analyze whether miR‐155 regulates RORα transcription. Secretion of inflammatory cytokines into sera in mice were measured by enzyme‐linked immunosorbent assay. Hematoxylin and eosin staining, alanine aminotransferase, and aspartate transaminase, assay were used to evaluate liver function. We found that MCPIP1 expression was notably upregulated and significantly downregulated inflammatory cytokine secretion and NF‐κB signaling activation in macrophages following exposure to lipopolysaccharide. Moreover, miR‐155, lowered by MCPIP1, directly targeted on 3′‐untranslated region of RORα to activate an inflammatory response. Importantly, MCPIP1 overexpression in mice alleviated septic liver injury symptoms following lipopolysaccharides stimulation. Collectively, these data highlight MCPIP1/miR‐155/RORα axis as a novel modulation of inflammation in liver injury and potential therapeutic target for future research. Abstract : We found that MCP‐1‐induced protein 1 (MCPIP1) expression was notably upregulated and significantly downregulated inflammatory cytokine secretion and nuclear factor‐κB (NF‐κB) signaling activation in macrophages following exposure to lipopolysaccharide. Moreover, miR‐155, lowered by MCPIP1, directly targeted on 3′‐untranslated region (3′‐UTR) region of retinoid‐related orphan receptor α (RORα) to activate inflammatory response. Importantly, MCPIP1 overexpression in mice alleviated septic liver injury symptoms following lipopolysaccharides stimulation.